Encoding Theory of Mind in Character Design for Pedagogical Interactive Narrative - Mei Si; Stacy C. Marsella (Advances in Human-Computer Interaction)
Computer aided interactive narrative allows people to participate actively in a dynamically unfolding story, by playing a character or by exerting directorial control. Because of its potential for providing interesting stories as well as allowing user interaction, interactive narrative has been recognized as a promising tool for providing both education and entertainment. This paper discusses the challenges in creating interactive narratives for pedagogical applications and how the challenges can be addressed by using agent-based technologies. We argue that a rich model of characters and in particular a Theory of Mind capacity are needed. The character architect in the Thespian framework for interactive narrative is presented as an example of how decision-theoretic agents can be used for encoding Theory of Mind and for creating pedagogical interactive narratives.